Technology, tasks and training - evidence on the provision of employer-provided training in times of technological change in Germany - Lukowski, Felix [Verfasser]; Baum, Myriam [Verfasser]; Mohr, Sabine [Verfasser] (My University, 2021)
"In the context of technological change and the ongoing transformation of the labour market, this paper investigates firms' employer-provided continuing training provision for employees with different skill requirements. Following human capital theory, firms invest in training when expecting higher returns than costs. From a theoretical point of view, only investment in employees in high-skilled jobs is reasonable. Empirically, this is not always the case. Using firm-level data from the BIBB Establishment Panel on Training and Competence Development, a fractional logit model is applied to answer which role technology use and task profiles play in employees' training participation. The results suggest that firms with a higher proportion of digital technology users provide more training. On the contrary, more working time spent with digital technologies is associated with less training. A potential explanation could be that after initial training in using digital technologies, there are substantial learning effects and employees become more experienced. Additionally, employees who more frequently perform complex tasks receive more training independent of their jobs' general skill requirements." (authors' abstract; BIBB-Doku)
Keywords: S 1.5 Weiterbildung; G 2.2.1 Technologisierung; 370; Weiterbildung; Betriebliche Weiterbildung; Digitale Medien; Mediennutzung; Technischer Wandel; Erwerbstätiger; Berufsanforderung; Weiterbildungsbeteiligung